2014
DOI: 10.1108/ijccsm-01-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on cocoa production in West Africa

Abstract: Purpose – The study aimed at examining the current and future impact of climate change on cocoa production in West Africa. Design/methodology/approach – A translog production function based on crop yield response framework was used. A panel model was estimated using data drawn from cocoa-producing countries in West Africa. An in-sample simulation was used to determine the predictive power of the model. In addition, an out-sample simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Numerous studies have examined the perceptions of farmers on such topics as the impact of climate change on cocoa yields [8,9,20,21], smallholder choice of cocoa production systems [22][23][24], the potential benefits of cocoa agroforestry [25,26] and advantages of REDD+ in cocoa production [13,27]. There is however, limited information on how farmers perceive the inclusion of climate change mitigation strategies into their land/farm management objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the perceptions of farmers on such topics as the impact of climate change on cocoa yields [8,9,20,21], smallholder choice of cocoa production systems [22][23][24], the potential benefits of cocoa agroforestry [25,26] and advantages of REDD+ in cocoa production [13,27]. There is however, limited information on how farmers perceive the inclusion of climate change mitigation strategies into their land/farm management objectives.…”
Section: Introductionmentioning
confidence: 99%
“…This theory takes into account the influence of the weather on crops in the analysis of agricultural production by combining rainfall and temperature into composite "aridity" indices. It assumes that weather variables as "costless" inputs to the production process Ceteris Paribus (Ofori-Boateng and Insah, 2014). It should be observed that studies carried out using this model conclude that climate change has very damaging effects on agriculture (Rosenzweig 1985;Robertson et al 1987).…”
Section: Theoretical Literaturementioning
confidence: 99%
“…It is an approach developed by Mendelsohn and al (1994) to assess the impact of climatic hazards on agricultural income. By considering farmers' income rather than yield, was a way to account for farmers' adaptation strategies Insah, 2011 and. The Ricardian model was criticized for assuming price constancy and also that adaptation strategies were cost-free (Cline, 1996;Deressa et al, 2005;Deschênes and Greenstone, 2007) thus underestimating the true impact of climate change.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…Based on the appraised annual full market worth of the cocoa sector of US $100 billion dollars [15], just around $6 billion dollars accrues to the 5 million growers who cultivate cocoa plants and those harvesting the beans in the West African region [16]. This level of socio-economic inequity together with the perceived ecological consequences of cocoa harvests in the producing nations of West Africa indicates that most consumption habits elsewhere usually leave in their wake grave problems which can no longer be ignored [17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%